2013
DOI: 10.1017/s0272263113000594
|View full text |Cite
|
Sign up to set email alerts
|

Processing Focus Structure in L1 and L2 French

Abstract: This study examined the event-related potentials (ERPs) elicited by focus processing among first language (L1) speakers and second language (L2) learners of French. Participants read wh-questions containing explicit focus marking, followed by responses instantiating contrastive and informational focus. We hypothesized that L2 proficiency would modulate nativelikeness in L2 processing. For the L1 and L2 groups, widespread word-long positive shifts reflected the processing of nouns receiving informational and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
6
38
0
Order By: Relevance
“…The present findings invite further investigation, for example, in the spirit of Reichle and Birdsong (2014), who examined ERP signatures generated during online processing of c'est -clefts, or Dekydtspotter and Farmer (2016), who studied the effects of structural priming in the processing of clefts. One limitation of this study is that our data do not let us directly judge whether the L2 speakers process c'est -clefts the same way as NSs.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The present findings invite further investigation, for example, in the spirit of Reichle and Birdsong (2014), who examined ERP signatures generated during online processing of c'est -clefts, or Dekydtspotter and Farmer (2016), who studied the effects of structural priming in the processing of clefts. One limitation of this study is that our data do not let us directly judge whether the L2 speakers process c'est -clefts the same way as NSs.…”
Section: Resultsmentioning
confidence: 70%
“…In Donaldson's (2012) spontaneous conversational data, no statistically significant differences were found between the near-native speakers’ use of c'est -clefts and that of their NS interlocutors; the near-native speakers felicitously used c'est -clefts to mark focus. Reichle and Birdsong (2014) examined ERP signatures for two groups of L2 French speakers at different proficiency levels via a discourse task with contrastive and informational focus. The ERP signatures of the high-proficiency group appeared entirely nativelike.…”
Section: L2 Acquisition Of the French C'est-cleftmentioning
confidence: 99%
“…Cowles (2003) found that native English speakers showed a sustained LAN effect corresponding to an increased WM load for contrastive focus, which is more WM-intensive than informational focus. Reichle (2010b) found an early negativity under similar conditions in L2 French, and this negativity was present for L2 learners of high proficiency (Reichle and Birdsong 2014). For the present study, we predicted that in discourse contexts where focus is licensed, a similar LAN would index the increased WM load required to track the focal referent across discourse, as compared to sentences with extraneous focus marking.…”
Section: |mentioning
confidence: 67%
“…High-proficiency L2 learners also use prominence cues to evoke a contrast between a prominent element and its alternatives. This has been observed with contrastive pitch accents in both L2-Dutch (Braun & Tagliapietra, 2011) and L2-English (Lee & Fraundorf, 2017) as well as with structural prominence cues, such as clefts, in L2-French (Reichle, 2010a;Reichle & Birdsong, 2014). For instance, Reichle and Birdsong (2014) examined English speakers' event-related potential responses while they read cleft sentences in L2-French.…”
Section: Processing and Remembering Prominent Materials In L1 And L2mentioning
confidence: 98%
“…Here, we examine how L2 learners process cues to one particular influence on discourse representation: cues to a contrast between one element and its alternatives. In L1-English processing, prominence cues, such as a contrastive pitch accent in speech or font emphasis in written text, prompt comprehenders to encode a set of alternatives to the prominent element and later rule out those alternatives when remembering the true facts of the discourse (Braun & Tagliapietra, 2010;Calhoun, 2009;Fraundorf, Benjamin, & Watson, 2013;Fraundorf, Watson, & Benjamin, 2010;Reichle & Birdsong, 2014). For example, you need to push the RED button, not the blue button helps L1 comprehenders rule out the mentioned alternative blue button in their later memory, but not the unmentioned green button.…”
mentioning
confidence: 99%